2002
DOI: 10.1523/jneurosci.22-19-08514.2002
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Analysis Reveals Striking Differences in the Structural Plasticity of Two Readily Identifiable Glomeruli in the Antennal Lobes of the Adult Worker Honeybee

Abstract: The primary antennal sensory centers (antennal lobes) in the brain of the honeybee are highly compartmentalized into discrete spheres of synaptic neuropil called glomeruli, many of which can be identified according to their predictable size and location. Glomeruli undergo significant changes in volume during the lifetime of the adult worker bee, at least some of which are activity dependent. This study tests the commonly expressed assumption that increases in neuropil volume are accompanied by an underlying in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 54 publications
(64 reference statements)
1
45
0
Order By: Relevance
“…We hypothesise that the enlarged glomerular volume may originate from reorganization of the neural network (e.g. changes in synapse number), as discussed earlier (Hourcade et al, 2009), but other mechanisms, such as glial growth cannot be included (Brown et al, 2002). It should be noted that this effect of pre-exposure was measured on the normalised glomerular volume, i.e.…”
Section: S L I T O R C O S L I T P R 6 S L I T P R 1 6 S L I T P R 1 mentioning
confidence: 82%
“…We hypothesise that the enlarged glomerular volume may originate from reorganization of the neural network (e.g. changes in synapse number), as discussed earlier (Hourcade et al, 2009), but other mechanisms, such as glial growth cannot be included (Brown et al, 2002). It should be noted that this effect of pre-exposure was measured on the normalised glomerular volume, i.e.…”
Section: S L I T O R C O S L I T P R 6 S L I T P R 1 6 S L I T P R 1 mentioning
confidence: 82%
“…In the template AL we did not find enlarged glomeruli in the T4 region. The difference between these two ALs probably reflects the interindividual variation, which might be, e.g., experience dependent (Winnington et al, 1996;Sigg et al, 1997;Brown et al, 2002Brown et al, , 2004. The arborization of ORNs in the glomeruli that we assigned to subpopulation T4 differed from the arborization of all other ORNs investigated.…”
Section: Innervation Pathways Of Orns Via T1-t4mentioning
confidence: 86%
“…Work on adult neuronal plasticity in the honeybee has demonstrated that increases in adult glomerular volume are activity-dependent and correlated with better learning performance (Winnington et al 1996;Sigg et al 1997). Quantitative electron-microscopic studies have lead to the suggestion that volume increase and synapse number changes are independent processes that both contribute to structural plasticity in the AL, although synapse reorganization might only play a minor role on neuropilar volume (Brown et al 2002). Age effects on bee mushroom body volumes must be distinguished from experience effects; the first 5 days of adult brain development seem to be functionally separated from later maturation effects (Farris et al 2001); this is supported by synapse counts in certain glomeruli (Brown et al 2004).…”
Section: Discussionmentioning
confidence: 99%